Health information system in nursing homes - Santos, S.; Oliveira, A. (ICERI2021 Proceedings, 2021)
The use of health information systems can bring benefits to long-term care services. They can help save time, support decisions, as they provide adequate, reliable information and at the right time. The main goal of this article is to model and develop a solution to help caregivers with their daily work and with this, improve the quality and effectiveness of the services provided to their patients. To understand the specific needs, we conducted a focus group study with direct care nursing home employees. Subsequently, a qualitative analysis was performed to define the requirements for the information system. The results obtained revealed the need to record and access health information quickly to make decisions, ensure the flow of information within the team and between shifts and the creation of automatic alerts to ensure procedures execution. After this phase, taking into account the defined requirements, the solution was conceptualized and developed. The evaluation and improvement of the prototype will be presented in a future paper.